The effects of combining elastic and free weight resistance on strength and power in athletes - Anderson, C. E.; Sforzo, G. A.; Sigg, J. A. (The Journal of Strength and Conditioning Research, 2008)
This study was undertaken to determine whether combined elastic and free weight resistance (CR) provides different strength and power adaptations than free weight resistance (FWR) training alone. Forty-four young (age 20 ± 1 years), resistance-trained (4 ± 2 years' experience) subjects were recruited from men's basketball and wrestling teams and women's basketball and hockey teams at Cornell University. Subjects were stratified according to team, then randomly assigned to the control (C; n = 21) or experimental group (E; n = 23). Before and after 7 weeks of resistance training, subjects were tested for lean body mass, 1 repetition maximum back squat and bench press, and peak and average power. Both C and E groups performed identical workouts except that E used CR (i.e., elastic resistance) for the back squat and bench press, whereas the C group used FWR alone. CR was performed using an elastic bungee cord attached to a standard barbell loaded with plates. Elastic tension was accounted for in an attempt to equalize the total work done by each group. Statistical analyses revealed significant (P < 0.05) between-group differences after training. Compared with C, improvement for E was nearly three times greater for back squat (16.47 ± 5.67 vs. 6.84 ± 4.42 kg increase), two times greater for bench press (6.68 ± 3.41 vs. 3.34 ± 2.67 kg increase), and nearly three times greater for average power (68.55 ± 84.35 vs. 23.66 ± 40.56 watt increase). Training with CR may be better than FWR alone for developing lower and upper body strength, and lower body power in resistance-trained individuals. Long-term effects are unclear, but CR training makes a meaningful contribution in the short term to performance adaptations of experienced athletes.